1989
DOI: 10.1161/01.res.65.5.1283
|View full text |Cite
|
Sign up to set email alerts
|

Protection by superoxide dismutase from myocardial dysfunction and attenuation of vasodilator reserve after coronary occlusion and reperfusion in dog.

Abstract: Previous studies indicate impairment of coronary arterial ring relaxation and loss of coronary vasodilator reserve after coronary artery occlusion and reperfusion. These changes are mediated in part through loss of endothelium-derived relaxing factor (EDRF) and/or myocardial neutrophil accumulation. To examine if superoxide dismutase (SOD), a scavenger of superoxide radicals, would modify the diminished coronary vasodilator reserve after temporary coronary occlusion in the intact animal, open-chest mongrel dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

1992
1992
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(28 citation statements)
references
References 44 publications
(34 reference statements)
0
26
0
2
Order By: Relevance
“…32 Ang II via AT 1 R activation has been shown to enhance NADH/NADPH oxidase activity. 27 Ox-LDL and TNF-␣ are also potent proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…32 Ang II via AT 1 R activation has been shown to enhance NADH/NADPH oxidase activity. 27 Ox-LDL and TNF-␣ are also potent proinflammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…23 Oligonucleotides containing the consensus sequence for activator protein (AP)-1 and nuclear factor (NF)-B were end-labeled with [␥- 32 P]ATP by use of T4 polynucleotide kinase and purified by use of Chroma Spin-10 columns (BD Biosciences). The labeled oligonucleotides were incubated with the nuclear fractions for 30 minutes at room temperature in 50 mmol/L Tris-HCl buffer, pH 7.5, containing 20% glycerol, 5 mmol/L MgCl 2 , 2.5 mmol/L EDTA, 2.5 mmol/L dithiothreitol, 250 mmol/L NaCl, and 0.25 mg/mL poly(dI-dC).…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%
“…In our rat model of myocardial ischemia/reperfusion, a continuous intravenous infusion of the free radical scavenger N-2-mercaptopropionyl glycine (MPG) during ischemia and reperfusion resulted in the prevention of the coronary endothelium-dependent relaxation in response to acetylcholine (9). There is also evidence in species other than rats that the reperfusion-induced endothelial injury is the consequence of the production of oxygen-derived free radicals because impaired endothelium-dependent relaxation can be restored by treatment with superoxide dismutase and catalase in both large coronary arteries (4,10) and the microcirculation (11).…”
Section: Mechanisms Of Reperfusion-induced Coronary Endothelial Dysfumentioning
confidence: 99%
“…Reperfusion of previously ischemic tissues results in endothelial dysfunction, increases in coronary vascular resistance, and extension of myocardial injury. 17,18 Activation of the renin-angiotensin system may play a critical role in this process, since cardioprotective effects have been observed with angiotensin-converting enzyme (ACE) inhibitors. 19,20 It was demonstrated that ACE inhibitors reduce infarct size and reperfusion arrhythmias and improve post-ischemic myocardial functional recovery.…”
Section: Discussionmentioning
confidence: 99%